2023
DOI: 10.1021/jacs.3c01766
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Two-Dimensional Violet Phosphorus P11: A Large Band Gap Phosphorus Allotrope

Abstract: The discovery of novel large band gap two-dimensional (2D) materials with good stability and high carrier mobility will innovate the next generation of electronics and optoelectronics. A new allotrope of 2D violet phosphorus P11 was synthesized via a salt flux method in the presence of bismuth. Millimeter-sized crystals of violet-P11 were collected after removing the salt flux with DI water. From single-crystal X-ray diffraction, the crystal structure of violet-P11 was determined to be in the monoclinic space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 106 publications
2
31
0
1
Order By: Relevance
“…Very recently, Cicirello and colleagues synthesized a new two-dimensional allotrope of violet phosphorus, dubbed violet-P 11 , using a salt flux method in the presence of bismuth. 136 The crystal structure of this allotrope from different views is shown in Fig. 7f.…”
Section: Fundamental Physicochemical Properties Of Elemental Phosphor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Cicirello and colleagues synthesized a new two-dimensional allotrope of violet phosphorus, dubbed violet-P 11 , using a salt flux method in the presence of bismuth. 136 The crystal structure of this allotrope from different views is shown in Fig. 7f.…”
Section: Fundamental Physicochemical Properties Of Elemental Phosphor...mentioning
confidence: 99%
“…Single-crystal XRD has revealed that violet-P 11 crystallizes in the monoclinic space group C2/c (15), with unit cell parameters of 9.166(6), 9.121 (6), and 21.803( 14) Å for a, b, and c, respectively. 136 Violet-P 11 exhibits substantial stability in ambient air even after being exfoliated for at least an hour.…”
Section: Atomic Structurementioning
confidence: 99%
“…[3][4][5][6][7] Moreover, previous theoretical calculations and experiments indicated the presence of numerous unexplored phosphorus polymorphs. [6,[8][9][10][11][12][13][14][15][16][17] Considering that various forms of phosphorus crystals have recently emerged as platforms for investigating unique electronic and optical properties in low dimensions, [18][19][20][21][22] the identification of a new structural phase of elemental phosphorus will be of critical importance to better design materials for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…[2] The crystal structure of type-V RP (violet or Hittorf's phosphorus) has been identified using single-crystal XRD [23] in 1966 and has recently attracted increasing research interest. [15][16]24] The crystal structure of type-IV RP (fibrous phosphorus) has been identified in a relatively recent study. [25] Both types-IV and V RP contain a tubular motif [P8]P2[P9]P2[ in their structures.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Moreover, previous theoretical calculations and experiments indicated the presence of numerous unexplored phosphorus polymorphs. [6,[8][9][10][11][12][13][14][15][16][17] Considering that various forms of phosphorus crystals have recently emerged as platforms for investigating unique electronic and optical properties in low dimensions, [18][19][20][21][22] the identification of a new structural phase of elemental phosphorus will be of critical importance to better design materials for various applications.…”
Section: Introductionmentioning
confidence: 99%